Response of Glutinous Corn (Zea mays var. Ceratina Kulesh) to Organic Fertilizer Application on Acidic Dry Land - Lusia, Maria; Paridawati, Ika; Marlina, Neni; Syahrir, Novrizal; Susiana; Nurrohma; Nunihlawati, Haperidah (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Acidic drylands are classified as suboptimal lands due to their low soil fertility, characterized by poor nutrient content, low organic matter, poor soil structure, and inadequate drainage. Glutinous corn is one of the corn varieties susceptible to acidic dryland conditions, although some varieties exhibit greater tolerance. This study aims to evaluate the effects of various types of organic fertilizers on acidic drylands and on the growth and yield of glutinous corn (Zea mays var. Ceratina Kulesh). The study was conducted at Jl. Sukarela, Km 7, Sukarame District, Palembang City, using a field experiment with a non-factorial Randomized Block Design (RBD) consisting of four treatments, each replicated six times. The treatments included: no organic fertiliser, chicken manure fertiliser (30 tons/ha), liquid organic fertiliser from vegetable waste (20 mL/L), and a combination of chicken manure fertiliser with vegetable waste POC. The parameters observed were plant height, number of leaves, cob length, cob weight per plant, cob weight per plot, dry stalk weight per plot, and weight of 100 seeds. The results showed an increase in soil fertility, as indicated by improved soil structure and a rise in soil pH from 5.3 to 6.5. The liquid organic fertiliser from vegetable waste, at a dose of 20 ml/L, was the most effective treatment, with an average cob weight per plant of 240.3 g (equivalent to 1.28 tons/ha).